2006
DOI: 10.2754/avb200675040561
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Intoxication of Common Carp (Cyprinus carpio L.) at Different Water Temperatures

Abstract: Common carp (Cyprinus carpio L.) were exposed to nitrite (1.45 mmol·l -1 NO 2 -) for 48 hours at 14 °C and 20 °C, in order to investigate the mechanism of nitrite poisoning at these water temperatures. The effect of nitrite exposure on fish was assessed on selected haematological and biochemical indicators of the blood. Moreover, nitrite accumulation in the blood, liver and muscle was measured. Nitrite exposure produced high levels of methaemoglobin (88.2 ± 3.3% and 92.9 ± 6.1%) at both water temperatures comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…A significant decrease in plasma Na + concentration was observed in group A 2 (35°C) compared with group A 1 (27°C). This result deviated from the observation of Jensen et al (1987) and Kroupova et al (2006), who observed slight decrease between the two groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in plasma Na + concentration was observed in group A 2 (35°C) compared with group A 1 (27°C). This result deviated from the observation of Jensen et al (1987) and Kroupova et al (2006), who observed slight decrease between the two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Adeyemo et al (2003) documented the haemato-logical response of Clarias gariepinus to changes in acclimation temperature. Kroupova et al (2006) worked on nitrite intoxication of common carp (Cyprinus carpio) at different water temperatures but no information is known about the influence of temperature on nitrite toxicity of the most cultured fish species in Nigeria, C. gariepinus.…”
Section: Introductionmentioning
confidence: 99%
“…; Kroupová et al . ). Important internal factors include the fish species, age, size and individual fish sensitivity (Eddy et al .…”
Section: Toxicitymentioning
confidence: 97%
“…; Kroupová et al . ). However, the latter factor may accelerate the process of fish recovery after nitrite poisoning (Huey et al .…”
Section: Toxicitymentioning
confidence: 97%
See 1 more Smart Citation